PENYIDIKAN TINDAK PIDANA KORUPSI (STUDI PENYIDIKAN DI POLRESTA MEDAN DAN KEJARI MEDAN) - Bambang Rubianto; Muhammad Hamdan; Mahmud Mulyadi; Suhaidi Suhaidi (Universitas Sumatera Utara, 2014)
Recently, corruption has been a serious public attention. Whether or not the criminal act of corruption develops cannot be separated from the element of law enforcer. To anticipate the development of corruption, the law enforcers take the steps, among other things, through the process of investigation. This step is a part of the government efforts to reenforces law under the term of criminal policy or from the aspect of criminal law enforcement policy. In Indonesia, investigating the criminal act of corruption is carried out by three institutions such as Police, Attorney and Corruption Eradication Commission (KPK), Due to the limitation of KPK, the investigation at regional level is focused in the Police and Attorney regional affice. The corruption investigation process cannot be separated from the problems related to technical and non-technical process of criminal justice system. In Medan and its vicinity, the investigation of the criminal act of corruption is focused on Medan Resort Police Departement and Medan Attorney Regional Office. The authority to do the investigation is legal according to the law. Yet, in practice, this authority is less optimally empowered by both institutions, in the scope of its job description in the past three years. To cope with less optimal investigation problem, in the future, Medan Resort Police Department and Medan attorney Regional Office will cooperate with the academicians to provide workshop or seminar, to make staff study, to schedule the investigation of the criminal act of corruption in the scale of priority, to increase the number of investigators, to synchronize the perception of investigators in corruption case investigation. The still rooted culture of corruption will be cahanged through investigating the cases of criminal act of corruption. Community participation in the process of corruption case investigation will be improved and the culture of discipline of government apparatuses will be optimalized.